Front Cover: In Situ Investigation of the Thermal Decomposition of Cl4(CH3CN)W(NiPr) During Simulated Chemical Vapor Deposition (Eur. J. Inorg. Chem. 32/2019). Issue 32 (14th August 2019) - Nolan, Michelle M.; Kim, Seo Young; Koley, Arijit; Anderson, Tim; McElwee‐White, Lisa
Abstract : The Front Cover shows a look inside CVD. Most characterization of chemical vapor deposition (CVD) precursors occurs under conditions different from those inside CVD reactors. This work used in situ Raman spectroscopy during simulated CVD to examine the gas phase decomposition of a known WNx Cy precursor. In combination with previous ex situ and computational studies, we now propose a decomposition mechanism for the tungsten imido complex Cl4 (CH3 CN)WN i Pr during CVD. This project was initiated with support from the National Science Foundation under grant CHE‐0911640. More information can be found in the Communication by L. McElwee‐White et al. For more on the story behind the cover research, see the Cover Profile .